Cohort profile: the DANish LIFE course (DANLIFE) cohort, a prospective register-based cohort of all children born in Denmark since 1980. Issue 9 (20th September 2019) - Bengtsson, Jessica; Dich, Nadya; Rieckmann, Andreas; Hulvej Rod, Naja
Abstract : Purpose: The DANish LIFE course (DANLIFE) cohort is a prospective register-based study set up to investigate the complex life course mechanisms linking childhood adversities to health and well-being in childhood, adolescence and young adulthood including cumulative and synergistic actions and potentially sensitive periods in relation to health outcomes. Participants: All children born in Denmark in 1980 or thereafter have successively been included in the cohort totalling more than 2.2 million children. To date, the study population has been followed annually in the nationwide Danish registers for an average of 16.8 years with full data coverage in the entire follow-up period. The information is currently updated until 2015. Findings to date: DANLIFE provides information on a wide range of family-related childhood adversities (eg, parental separation, death of a parent or sibling, economic disadvantage) with important psychosocial implications for health and well-being in childhood, adolescence and young adulthood. Measurement of covariates indicating demographic (eg, age, sex), social (eg, parental education) and health-related factors (eg, birth weight) has also been included from the nationwide registers. In this cohort profile, we provide an overview of the childhood adversities and covariates included in DANLIFE. We also demonstrate that there is a clear social gradient in the exposure to childhood adversities confirming clustering of adverse experiences within individuals. Future plans: DANLIFE provides a valuable platform for research into early life adversity and opens unique possibilities for testing new research ideas on how childhood adversities affect health across the life course.